Cianjur Earthquake Disaster Management Team Management - Didin Syaefudin; Wilda Fauzia; ‎ Ita; Hendik Wicaksono (JOURNAL EDUCATIONAL OF NURSING(JEN), 2022)
Earthquakes are disasters that tend to occur in Indonesia, these incidents are influenced by two factors, namely the geological location of Indonesia which is at the meeting of 3 large lithospheric plates consisting of the Eurasian, Pacific, and Indo-Australian plates, and the second factor is that the Indonesian region is formed from a combination of various micro continental plates and volcanic arcs where this gives rise to various types of faults that are spread across various regions of Indonesia (Rusdi et al., 2022). Immediate handling of earthquake disaster victims is the right of every individual to obtain social, economic, and health protection. Earthquake disaster management is a series of activities carried out to control disaster situations and prepare a framework to help people affected by disasters. This study aims to determine the Management of the Cianjur Earthquake Disaster Management Team. This study uses a quantitative descriptive research method. The results of this study prove that earthquake survivors in the village of Kampung Wangun Bone, Cianjur, West Java, as many as 61 people have been handled in terms of health problems. The conclusion obtained is that the management of the Cianjur Earthquake Disaster Management Team successfully handled 61 earthquake survivors in Bone Village, Cianjur, West Java.